PERBEDAAN BESAR FORCE DARI BEBERAPA ELASTOMERIC CHAIN: DIFFERENT FORCE OF SOME ELASTOMERIC CHAINS - Muslim Yusuf (Dentika: Dental Journal, 2010)
Elastomerics is the one of orthodontic’s components which is used to move the teeth by archwire movement to the slotbracket. Elastomeric products consist of ligature and chain. Elastomeric chain force depends on several factors such asmanufacturing process, duration and range of stretching. The obejective of this study was to know the effect of range andduration of elastomeric stretching force. This study used elastomeric chain from three different manufacturers. Samplewas stretched at 20 percent, 30 percent and 40 percent. It was stored in artificial saliva that connected with thermostat at37oC. Force was measured with correx. The result showed that there was no significant difference of force among threedifferent ranges. On the contrary duration of stretching elastomeric chain showed significant different force. In conclusion,the longer stretching distance of these elastomeric chains showed bigger initial force and smaller force decay. The forcedecay of these elastomeric chains decreased extremely on the first day and simultaneously decreasing on the next day.